Membangun Ekosistem Pendidikan Unggul: Peran Lembaga Sosial Sebagai Pilar Transformasi Pendidikan (Indo-MathEdu Intellectuals Journal, 2026)
The low quality of education in Indonesia shows that improving the quality of education cannot be achieved only through the role of formal education institutions, but requires the synergy of various social institutions. This research aims to analyze the contribution of social institutions in building a superior, inclusive and transformative educational ecosystem. The research uses a library study method by reviewing various scientific articles obtained from Google Scholar, ERIC, Scopus, and SINTA. Data were analyzed through stages of data reduction, synthesis, and drawing conclusions to identify the role of each social institution in providing education. The results of the study show that the family plays a role as a primary socialization agent that shapes students' basic character and values, schools as providers of formal education that develop academic competencies, religious institutions as reinforcers of moral and spiritual values, legal institutions as guarantors of certainty and protection of educational rights, and economic institutions as supporters of providing resources and access to education. The synergy between these institutions forms an educational ecosystem that supports each other in improving the quality of learning, equitable access and character formation. Thus, strengthening collaboration between social institutions is an important strategy for realizing education that is sustainable, inclusive, and oriented towards improving the quality of human resources